Analisis SWOT Pelaksanaan Magang Studi Kasus di MIN 7 Kota Medan: Penelitian - Nadia Salsabila Putri; Mutiara Putri Nabila; Zahra Mutiara; Nadilla Indriani Nasution; Sindy Anzani; Salim (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to describe the implementation of Internship 1 at MIN 7 Medan City and analyze the school's conditions through a SWOT approach as part of the development of professional competencies for prospective teachers. The study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation, carried out by five students from the PGMI Study Program at Medan State University in October 2025. The results show that MIN 7 Medan City has strengths in the form of A accreditation, a clear organizational structure, adequate teaching staff competencies, and adequate classroom conditions, while several aspects such as limited land, parking area, warehouse management, and the unavailability of science laboratories still need to be strengthened. On the other hand, the madrasah has opportunities for development through government support, high public trust, and cooperation with committees and the surrounding community, while the challenges faced are more external factors such as limited land and access to the location. Internship 1 provides students with real-world experience in understanding school management and developing adaptive skills as preparation for their future careers as educators.